2015
DOI: 10.1007/s00253-015-6674-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tryptophol on the bacteriophage infection in high-temperature environment

Abstract: Small metabolites can participate in the virus-host interactions in eukaryotes. However, little is known about roles of metabolites in the interactions between bacteria and bacteriophages. In this study, the metabolomic profilings of bacteriophage GVE2-infected and virus-free Geobacillus sp. E263, a thermophilic bacterium isolated from a deep-sea hydrothermal vent, were characterized. The results showed that metabolites tryptophol, adenine, and hydroxybenzylalcohol were significantly elevated in Geobacillus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Moreover, IE inhibits bacteriophage replication in a thermophilic bacterium, Geobacillus sp. E263 39 , virus replication in shrimps 40 , and proliferation of parasitic protozoa 41 . Also ILA is reported to have antifungal activity against Penicillium strains 42 and anti-bacterial activity against E. coli and B. cereus 43 .…”
Section: Tryptophan Catabolites As Signals and Antimicrobial Agentsmentioning
confidence: 99%
“…Moreover, IE inhibits bacteriophage replication in a thermophilic bacterium, Geobacillus sp. E263 39 , virus replication in shrimps 40 , and proliferation of parasitic protozoa 41 . Also ILA is reported to have antifungal activity against Penicillium strains 42 and anti-bacterial activity against E. coli and B. cereus 43 .…”
Section: Tryptophan Catabolites As Signals and Antimicrobial Agentsmentioning
confidence: 99%
“…Gluten is a major dietary component in wheat, rye and barley, and consists of proteins that are partially resistant to proteolytic digestion due to a high content of proline and glutamine 1 , 2 . Large gluten peptides including gliadin escape gastric digestion and accumulate in the small intestine, where they may interact with the immune system 3 , 4 , affect the intestinal permeability 5 – 7 , and modify the gut microbial activity 8 , 9 . However, beyond the reduction in gluten, a low-gluten dietary regime also entails a replacement of dietary fibres of gluten-rich cereals such as wheat, rye and barley with dietary fibres from other sources.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the isolated compounds, gas chromatography coupled mass spectrometry (GC-MS) was conducted as described previously [ 12 ]. Briefly, the compound was silylated with trimethylsilyl cyanide and then analyzed on a Q Exactive GC Mass Spectrometers (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, there may be a relationship between tumor cell metabolic disorder and virus-induced host metabolic disorder. Our previous study showed that when the bacteria were challenged by bacteriophage, they could generate some special metabolites [ 12 ]. The bacteriophage-challenged bacterial metabolites may be an important resource of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%